Pengaruh Electronic Word of Mouth (E-Wom) Melalui Media Sosial Terhadap Minat Beli pada Produk Kosmetik Maybelline - Dedi Iskamto; Amalia, Erika (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Advancements in information technology and the internet have transformed how people communicate and share information. E-WOM. Maybelline is one of the most popular and recognizable cosmetic brands, as seen by its #1 sales ranking in Indonesia. This study aims to determine the effectiveness of Maybelline's e-WOM strategy on social media influences consumers' intentions to make purchases. This is inspired by the occurrence and corroborating data showing, although Maybelline has the highest sales proportion of any cosmetic brand in Indonesia, that percentage has been declining year. Furthermore, this research aims to determine the relationship and effect of each element, including information quality, quantity, reliability, usefulness, adoption information, and purchase intention. This study employs a quantitative methodology. Data were gathered through a questionnaire and analyzed using structural equation modeling (SEM) with SmartPLS software. The findings show that information usefulness is positively and significantly impacted by information quantity, quality, and credibility. Adoption of information is positively and significantly impacted by information quality, quantity, reliability, and usefulness. Information adoption has a positive and significant effect on purchase intention. In order to forecast information uptake, this study advises adding more factors related to information quality, quantity, and trustworthiness. Furthermore, the same concept may be applied by future researchers to more niche social media networks.